2016
DOI: 10.15171/jrip.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lactulose supplementation on fecal microflora of patients with chronic kidney disease; a randomized clinical trial

Abstract: Introduction: Lactulose is a prebiotic with bifidogenic and urea reduction effects. It can improve Bifidobacteria and Lactobacilli counts in healthy humans and it may possibly have similar effects in chronic kidney disease (CKD) patients. Objectives: To investigate the effect of lactulose on fecal microflora of patients with CKD. Patients and Methods: Thirty-two patients with stages 3 and 4 of CKD (43.8% male with mean age of 58.09±12.75 years) were randomly assigned to intervention (n=16) and control (n=16)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 34 publications
(33 reference statements)
1
24
1
3
Order By: Relevance
“…This phenomenon can further contribute to the urea lowering effect observed in our HAM‐RS2 ESRD patient and in CKD animals, C‐ Earlier studies have demonstrated marked increase in secretion of creatinine (51) by colonic epithelium in CKD animals. Consumption of lactulose has been shown to further enhanced fecal excretion of nitrogenous waste products, favorably change microbiome and attenuate inflammation in patients with CKD . Therefore, enhanced viability of colonic epithelium with consumption of HAM‐RS2 can, in part, contribute to unloading of waste products and its lower serum concentration, and D‐ The slow transit rate of colonic contents marked by constipation which is a common feature of CKD can limit intestinal secretion of creatinine by lowering their concentration gradient and reducing the liquidity of the medium which is essential for secretion of solutes by epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can further contribute to the urea lowering effect observed in our HAM‐RS2 ESRD patient and in CKD animals, C‐ Earlier studies have demonstrated marked increase in secretion of creatinine (51) by colonic epithelium in CKD animals. Consumption of lactulose has been shown to further enhanced fecal excretion of nitrogenous waste products, favorably change microbiome and attenuate inflammation in patients with CKD . Therefore, enhanced viability of colonic epithelium with consumption of HAM‐RS2 can, in part, contribute to unloading of waste products and its lower serum concentration, and D‐ The slow transit rate of colonic contents marked by constipation which is a common feature of CKD can limit intestinal secretion of creatinine by lowering their concentration gradient and reducing the liquidity of the medium which is essential for secretion of solutes by epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since over 50 years, lactulose has been considered the “bifidus factor”, increasing fecal Bifidobacterium counts [ 68 ]. A number of subsequent studies have confirmed increased intestinal content of Bifidobacterium [ 69 75 ] and Lactobacillus [ 69 , 72 ] in human stool samples upon lactulose exposure. Those studies relied on conventional microbiological techniques and did not address the overall composition of the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the potential safety concerns about the use of these agents (e.g., drug-induced nephrotoxicity and electrolyte disturbances) 5,128 may lead to possible undertreatment of constipation in patients with CKD, which could potentially contribute to their excess morbidity and mortality. In this context, the unique pharmacological properties of a few constipation agents, such as lactulose, a chloride channel activator (lubiprostone), and a guanylate cyclase C agonist (linaclotide), [19][20][21]129 may deserve special attention. In a study using an adenineinduced renal failure mouse model, Mishima et al 19 demonstrated that lubiprostone ameliorated the progression of CKD and the accumulation of uremic toxins by improving the gut microbiota and intestinal environment, suggesting its therapeutic potential for CKD.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%